Contaminant Removal and Precious Metal Recovery by Lateral Channel Filtration in Mining-Impacted Alluvial Floodplains - Johnson, William P.; Pazmiño, Eddy; Frederick, Logan; Ron, Cesar; Chica, Andrea; Tapia, Luis (Frontiers in Water, 2020)
Water quality impacts from artisanal and small-scale alluvial (placer) gold mining operations occur in developing economies across several continents including Asia, Africa, and South America. They often occur in remote and/or resource-poor settings in which mitigation strategies must contend with extreme seasonal variation in river flow as well as the economic incentive to periodically churn (mine) alluvial floodplains without riparian restoration. A novel strategy addressing these constraints is herein explored which employs the alluvial floodplain for filtration-driven removal of particulate contaminants and gold from streams. This process of lateral channel filtration is explored in the Rio Nambija of southern Ecuador, in terms of success in achieving the hydraulic objective of passively driven lateral flow, and the corresponding removal of particulate contaminants (e.g., total mercury, lead, iron, and manganese) by filtration. Accumulation of gold was examined to evaluate whether incorporation of this proposed practice in alluvial (placer) mining can reduce particle-bound contaminants in streams and simultaneously increase economic benefit.